O plágio sob o ponto de vista da teoria dialógica: ato ético e responsabilidade autoral - Leite, Patrícia Gomes de Freitas (2021)
This work has as its research object the linguistic and discursive elements that participate in the composition of the plagiarism considered in the whole of the enunciation. As for the theoretical contribution, it follows the guidance of the Bakhtin Circle, taking as analytical categories the notions of text, utterance, speech genres, sphere of human activity, dialogue, ethics, responsibility, authorship, non-alibi, meaning and theme proper to the conception dialogic language. Its general objective is to systematize, under the point of view of dialogic theory, a proposal for understanding the linguistic-discursive elements that participate in the configuration of plagiarism and, therefore, distinguish plagiarism from non-plagiarism. The research methodology is theoretical and bibliographic in an exploratory nature with an emphasis on the in- depth documentary-analytical study of the writings of the Bakhtin Circle. As for the corpus, we chose samples of utterance used in the internet universe, by observing the living context of production of these utterances extracted from the media sphere, more specifically from genres that circulate on social networks, such as Instagram and WhatsApp, as well as utterances belonging to academic, artistic-literary and artistic- musical genres. The dialogic analysis of these utterances, in which theory and analysis are worked together, is qualitative and critical with attention focused on the elements that co-occur in the constitution of plagiarism and that, consequently, can characterize an unreferenced copy as not being plagiarism from the point of view of dialogic discourse analysis. The conclusion brings an end to the study with emphasis on the distinction between the notions of text and utterance as being capital in our understanding that there is no plagiarism of utterance, but of text and that genre and sphere are the elements of the architecture of the enunciation that weigh the most socioculturally in the characterization of the copy not referenced as plagiarism or as non-plagiarism.